Investigation of serum and milk acute phase proteins level in goats with experimentally infected staphylococcus aureus subclinical mastitis - Tajol Ariffin, Muhammad F; Chai, M Hian; Sukiman, Muhammad Z; Ghazali, Mohd F; Zainal Ariffin, Siti M (ResearchersLinks, 2022)
Mastitis is an inflammatory condition of the mammary gland which is usually caused by a bacterial infection. This study aims to determine acute phase protein (APP) and its association with somatic cell count (SCC) during experimentally induced subclinical mastitis in goats. Thirty lactating goats were divided into two groups (n=15 per group) challenged either by intramammary infusion of 1 x 103 cfu/mL Staphylococcus aureus (S. aureus) or phosphate-buffered saline (control). The haptoglobin (Hp), serum amyloid A (SAA) and α1-acid glycoprotein (AGP) levels in serum and milk were measured at pre-and post-infection (6, 24, 48 and 72 h) using the ELISA method. The SCC was determined by the direct microscopic method. Results revealed a time-dependent change of Hp, SAA and AGP in the infected group compared to the control. The APP levels in the milk were significantly higher (p<0.05) than those in the serum. A significant good correlation between milk Hp concentration and SCC was observed (rs= 0.73, p<0.05). However, there were no associations between milk SAA and AGP concentrations with SCC respectively. In conclusion, altered expression of the serum and milk APPs was seen during S. aureus-induced subclinical mastitis infection in goats, which unlock the potentials of APP evaluation as alternative tools for early diagnosis of subclinical mastitis in goats. Also, there was a significant relationship between milk Hp and SCC, thus reflecting the intensity of the inflammatory response to mammary tissue.